Atomic force microscopy imaging of ZnO nanodots deposited on quartz by sparking off different tip shapes - T. Kumpika (2018)
We have demonstrated a simple method for depositing ZnO nanodots on quartz substrates by sparking off different tip shapes at voltages of 2, 4 and 6 kV in air at atmospheric pressure. A comparison was made among the three tip shapes: the sharp tip, the conical tip and the dull tip. The surface morphology was then observed by atomic force microscopy. The mean height of the randomly distributed dots of approximately 8 nm was successfully deposited from the sharp tip at 6 kV. Characterizations by UV-vis spectroscopy and Raman spectroscopy have confirmed the presence of ZnO and the quality improvement by annealing treatments. Moreover, a nucleation mechanism of the nanodot formation is discussed. Copyright © 2006 John Wiley & Sons, Ltd.